The mapping of full weld cycle heat profile for friction stir welding pipe butt joints - Ismail, A. (Springer Verlag, 2018)
Aluminium alloy 6063 pipe sections were friction stir welded to produce a sound joining. In this present study, the full weld cycle of heat input will be gathered for rotational speed ranging between 1000 and 1600 rpm and travel speed between 3 and 5 mm/s. There will be 5 specimens to be friction stir welded. It was found that, the heat input will be increased with the increment of rotational speed up to 396 °C and decreased with the increment of travel speed with a minimum of 221 °C. These conditions were recorded by utilizing K-type thermocouples and the Signal Express software with a National Instrument model cDAQ-9171 data logger. © Springer International Publishing AG 2018.